Antara Ekologi, Religi, dan Tradisi: Menyigi Makna Kultural Nama Sumber Mata Air di Kabupaten Banyuwangi (Kajian Antropolinguistik) - Saputra, Oky Dhani; Zakiyah, Millatuz (Universitas Muhammadiyah Surabaya, 2025)
This research uses a qualitative descriptive method with an anthropolinguistic approach. The data source in the research is the caretaker at each water source. The data in this research are the result of an anthropolinguistic review of the cultural meaning of the names of water sources in Banyuwangi. Data collection techniques were carried out through structured interviews and observations of the caretakers of each water source. Data analysis consists of (1) identifying the naming of each water source; (2) classifying the names of water sources based on their naming patterns and functions; (3) linking naming to its function and cultural background; and (4) describe and analyze the data found. The results of this research are (1) there is a pattern in the naming of fountains at water sources in Banyuwangi; (2) there is a cultural background and influence of Hindu religion on the patt Water Sources, Cultural Significance.